Student perceptions of and attitudes towards digital health education and technology - Jandra Sule (Proceedings of the Estonian Academy of Sciences)
Digital health education and an understanding of effective technology application are essential for shaping the clinical environments of the future. This requires an understanding of nursing studentsâ attitudes and behaviours in health education. The objective of this study was to investigate nursing studentsâ perceptions of and attitudes towards digital health technologies. The study employed a qualitative research method focusing on the independent work of the students enrolled in the 2023/2024 Digital Technologies in Health course. Qualitative data were collected through Moodle, the common e-learning platform at Tallinn Health University of Applied Sciences. The document analysis database consisted of 185 student self-reflections and self-assessments. Trust in technology and the use of software emerged as key factors in the learning process. Students recognised the importance of quality health data and demonstrated trust in utilising electronic records, even when lacking previous experience. Despite their positive attitudes towards digital technologies, significant challenges remain in the application of fundamental digital skills. The most pressing concerns are related to digital literacy and innovation. Students perceive the use of digital tools as potentially distancing healthcare professionals from patients, which raises ethical concerns, particularly in relation to their future professional roles. Nursing educators should prioritise fostering a strong professional nursing identity, with particular emphasis on the positive impact of digital health technologies in clinical practice.